A systematic review and meta-analysis of intervention studies on mathematics and science pedagogical content knowledge - Fukaya, Tatsushi; Nakamura, Daiki; Kitayama, Yoshie; Nakagoshi, Takumi (Frontiers in Education, 2024)
Pedagogical content knowledge (PCK) has been considered as professional knowledge that teachers need to effectively instruct students. Empirical studies have been conducted to enrich teachers' PCK through interventions such as professional development programs. In this study, we conducted a systematic review and meta-analysis of studies about PCK interventions and their quantitative evaluation among mathematics or science teachers at the elementary and secondary education levels. We identified 101 effect sizes (42 for multiple group comparison designs and 59 for multiple time point comparison designs) and found that the interventions had a positive effect in both designs. The results of the meta-regression analysis showed that in the multiple group design, the effects differed by intervention target, with higher scores for the PCK intervention than for the CK-only intervention, and in the multiple time point design, the effects differed by subjects treated, with higher scores for the science materials than for the mathematics materials. These results not only demonstrate the average effectiveness of previous studies aimed at improving teachers' PCK but also provide insights into effective designs for professional development methods that promote PCK acquisition.